SELEÇÃO DE GENÓTIPOS F2RC1 DE TOMATEIRO PARA PROCESSAMENTO COM ALTOS TEORES DE ACIL-AÇÚCARES E RESISTENTES A ARTRÓPODES-PRAGA - Dias, Diego Munhoz (2015)
Tomato is a crop of great importance as a source of income and jobs in the horticulture. However, this crop has several barriers that hinder its cultivation, among them pests attacks should be highlighted. To reduce the damage caused by pests, the development of cultivars with satisfactory levels of resistance is a viable alternative. In this sense, this research aimed to select F2BC1 genotypes with high contentes of acyl sugars (AS) and evaluate their resistance to spider mite (Tetranychus urticae), pinworm tomato (Tuta absoluta) and whitefly (Bemisia tabaci biotype B). Plants of the F2 generation from the interspecific cross between the wild access Solanum pennellii LA-716 and the commercial line Redenção (Solanum lycopersicum) were selected for resistance to arthropod pests and backcrossed with its recurrent parent Redenção and advanced to the F2BC1 generation. Tests were performed to evaluate arthropod pests resistance and the bioassays evaluated eight genotypes selected with high contents of AS, four genotypes selected with low contents of AS and their parents were used as checks. Genotypes with high contents of AS usually presented the best levels of pests resistance. Significant correlation was obtained between the AS content and the evaluated resistance parameters, confirming the association between high contents of AS with pests resistance. The selection was effective in the differentiation of genotypes with contrasting acyl sugars contents and facilitated the selection of F2BC1 processing tomato genotypes resistant to Tetranychus urticae, Tuta absoluta and Bemisia tabaci biotype B. Among the selected lines, those with high levels of acyl sugars, i.e. RVTA-2010-31-pl # 177, RVTA-2010-83-pl # 357 and RVTA-2010-31-pl # 347, presented the best results for resistance to arthropods pest.